Review of Oral and Dental Consideration in the Patients with Head and Neck Radiotherapy and Chemotherapy - Bakhshi, Mahin; Mortazavi, Melika Sadat; Tofangchiha, Maryam; Afraz, Elham Sadat; Gholami, Shahzad; Bakhtiari, Sedigheh (Journal of Dental School, 2018)
Objectives Aggressive cancer therapy places patients at a greater risk for oral complications. Cancer patients suffer from oral toxic effects secondary to antineoplastic therapy (radiotherapy and chemotherapy). The aim of this review is management of the head and neck cancer patients that specifically emphasizes the prevention and treatment of oral and dental complications associated with cancer therapy. Methods In this narrative review article, the specialized databases such as PubMed, PubMed Central, MEDLINE, EBSCO, Science Direct, Scopus from 2008 to 2018 were used to find relevant documents by using Mesh terms: Chemotherapy, Radiotherapy, oral consideration, head and neck. Results The data were categorized in: Complications of head and neck radiotherapy and its management (Xerostomia, Oral Infection, Oral Mucositis, Osteoradionecrosis), Complications of head and neck chemotherapy and its management (Mucosal toxicity, Dental alterations, Neurological disorders, Salivary alterations, Dysgeusia, Infections, Bleeding tendency, Osteonecrosis of the jaws due to bisphosphonates). Conclusion In order to minimize morbidity in the head and neck cancer patients, it is recommended for consulting to dental health care providers before, during and after cancer therapy.